1997
DOI: 10.1016/s0735-1097(96)00446-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dihydrocodeine on Chemosensitivity and Exercise Tolerance in Patients With Chronic Heart Failure

Abstract: Augmented chemosensitivity is important in the pathophysiology of chronic heart failure. Its suppression with dihydrocodeine was associated with a reduction of exercise ventilation, an improvement in exercise tolerance and a decrease in breathlessness. Pharmacologic modulation of chemosensitivity may benefit patients with chronic heart failure and merits further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
92
1
9

Year Published

1999
1999
2016
2016

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 131 publications
(103 citation statements)
references
References 34 publications
1
92
1
9
Order By: Relevance
“…Dihydrocodeine can reduce breathlessness and improve exercise tolerance in CHF, most likely by a reduction in chemosensitivity. 13 In the present study, dihydrocodeine administration caused a decrease in peripheral chemosensitivity (Ϫ40% versus placebo) with concomitant changes in the periodic respiratory pattern.…”
Section: Discussionmentioning
confidence: 45%
See 1 more Smart Citation
“…Dihydrocodeine can reduce breathlessness and improve exercise tolerance in CHF, most likely by a reduction in chemosensitivity. 13 In the present study, dihydrocodeine administration caused a decrease in peripheral chemosensitivity (Ϫ40% versus placebo) with concomitant changes in the periodic respiratory pattern.…”
Section: Discussionmentioning
confidence: 45%
“…13 Eight patients with a cyclical respiratory pattern received placebo or dihydrocodeine (1 mg/kg body wt) on 2 separate days in a randomized double-blind design.…”
Section: Effect Of Dihydrocodeine On Cyclical Respirationmentioning
confidence: 99%
“…These findings suggest that at least in patients with preserved exercise capacity, an elevated ventilatory response to exercise may be related to abnormal reflex responses from the periphery. Further support for this mechanism comes from therapeutic studies that show that changes in the activity of chemoreceptors (with oxygen or opiates) 20 or muscle ergoreceptors (with exercise training) 10 can favorably affect the ventilatory response to exercise.…”
mentioning
confidence: 99%
“…Small studies found that opioids are safe and effective for treatment of dyspnea in advanced HF patients 224 and reduce dyspnea and fatigue in patients with NYHA functional class II HF. 225 Paroxetine is effective for management of depression. 226 Thigh muscle strengthening is effective at reducing dyspnea and fatigue.…”
Section: End-of-life Carementioning
confidence: 99%